Protocolo de cuidados de enfermagem para monitorização glicêmica de pessoas com diabetes mellitus hospitalizadas - Frota, Gesiane Araújo (2022)
Diabetes Mellitus (DM) is a metabolic disorder, which causes glycemic alterations, which must be detected early and treated in order to avoid immediate and long-term complications. The use of care protocols in the care of people with glycemic disorders is an important tool for standardization of conduct. Objective: To develop a nursing care protocol for glycemic monitoring of people with type 2 Diabetes Mellitus, hospitalized at the Hospital Universitário Getúlio Vargas/Manaus/AM. Method: This is a methodological research in which the following steps were taken: a) carrying out an integrative review of the literature on the subject; b) search for consensus in the main scientific societies on DM and other protocols on the subject; c) construction of analytical tables with the selected texts; d) selection of contents of interest for the protocol; e) elaboration of the protocol text; f) preliminary evaluation of the protocol by seven nurses who work at the institution. Results: they are presented in two items: a manuscript about the protocol development process and the protocol, which is the technological product, e. The protocol was prepared from a literature review based on 15 studies, together with consensus and other protocols of scientific societies on the subject, for the development of the document. The protocol is composed of 11 items: Introduction; Objective; Risk factors for glycemic alterations; Glycemic targets; Signs and symptoms of hyperglycemia and hypoglycemia; Technical procedures for measuring capillary blood glucose; Nursing conducts according to blood glucose results; General nursing care for glycemic monitoring; Nursing process related to glycemic monitoring; New technologies for glycemic monitoring; Flowchart, in addition to a Standard Operating Procedure on the verification of capillary blood glucose which is an appendix to the protocol. The critical assessment of seven nurses was favorable, both in terms of clarity and the relevance and applicability of the protocol. The manuscript presents the protocol development process called: “Development of a Glycemic Monitoring Protocol in Hospitalized Persons with Type 2 Diabetes Mellitus” which followed the phases defined in the method and are presented as the basis of support for the construction of the protocol. Final considerations: The protocol produced meets the criteria of an evidence- based production and may guide Nursing care in glycemic monitoring, enabling better control of the condition, in addition to enabling a reduction in health costs